Versatile methods for synthesizing organic acid salts of quaternary berberine-type alkaloids as anti-ulcerative colitis agents. Issue 6 (2nd June 2016) - Zhang, Zhi-Hui; Li, Jing; Zhang, Hai-Jing; Deng, An-Jun; Wu, Lian-Qiu; Li, Zhi-Hong; Song, Hong-Rui; Wang, Wen-Jie; Qin, Hai-Lin
Abstract: Two versatile methods to synthesize kinds of organic acid salts of quaternary berberine-type alkaloids were investigated in order to determine which is more efficient to improve the liposolubility of the target compounds and to explore the efficacy of the target compounds as anti-ulcerative colitis (UC) agents. Overall evaluation according to the reaction results and yields of the final products indicated that the synthetic method using tertiary (±)-8-acylmethyldihydroberberine-type alkaloids as key intermediates is superior to that of using tertiary dihydroberberine-type alkaloids as intermediates. Ten target compounds were synthesized using quaternary berberine chloride and quaternary coptisine chloride as starting materials, respectively, and the anti-UC activity of some target compounds was evaluated in an in vitro x-box-binding protein 1 (XBP1) transcriptional activity assay using dual luciferase reporter detection. At 10 μM, the tested compounds were found to activate the transcription of XBP1 target at almost the same level as that of quaternary coptisine chloride. The synthesized target compounds were also found to share higher liposolubility than the inorganic acid salts of quaternary berberine-type alkaloid.